2023
DOI: 10.1002/star.202200281
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Chinese yam (Dioscorea opposita Thunb.) in High‐Fat Diet/Streptozotocin‐Induced Diabetic Rats

Abstract: This study aims to assess the effect of different doses of Chinese yam (CY) on a high‐fat diet (HFD) and a streptozotocin‐induced diabetic rat model, using resistant starch (RS) as a positive control. Rats in the normal control and diabetes model (DM) groups are fed the standard diet and HFD, respectively. The RS and CY‐intervention groups are fed with a special HFD, in which starch, maltodextrin, and sucrose in the HFD are replaced completely with RS or CY powder in different proportions: 33.33% (1/3), 66.67%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…According to the ancient Chinese pharmacopoeia "Compendium of Materia Medica", yam was recorded to be conducive to nourishing the spleen and stomach, strengthening immunity, and delaying ageing. Furthermore, emerging evidence has demonstrated that the bioactive ingredients of yam possess many other potential health benefits such as antioxidant [14], anti-inflammatory [15], antitumor [16], anti-diabetic [17], and anti-obesity and hypolipidemic [18] activities. However, the research lipid-lowering activity is frequently limited to studies on single components or extracts of yam [19,20], and it is unclear whether yam maintains similar effects when consumed as a whole food.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ancient Chinese pharmacopoeia "Compendium of Materia Medica", yam was recorded to be conducive to nourishing the spleen and stomach, strengthening immunity, and delaying ageing. Furthermore, emerging evidence has demonstrated that the bioactive ingredients of yam possess many other potential health benefits such as antioxidant [14], anti-inflammatory [15], antitumor [16], anti-diabetic [17], and anti-obesity and hypolipidemic [18] activities. However, the research lipid-lowering activity is frequently limited to studies on single components or extracts of yam [19,20], and it is unclear whether yam maintains similar effects when consumed as a whole food.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The native YS mainly falls into the RS2 category, possessing inherent compactness that imparts digestive resistance but becomes susceptible to digestion upon cooking. [6] To retain intrinsic antidigestive attributes of YS, modifications are imperative. Recent studies have identified the emergence of a novel RS variant, classified as RS5, which involves the introduction of fatty acids or polyphenols into the hydrophobic cavity of amylose.…”
Section: Introductionmentioning
confidence: 99%